GAMBARAN FAKTOR YANG MELATARBELAKANGI PENDERITA KUSTA DALAM MELAKUKAN PRAKTIK PENCARIAN PENGOBATAN KUSTA (Studi Pada Penderita Kusta Baru Tahun 2016 di Kabupaten Blora) - Ria Nur Madyasari; Lintang Dian Saraswati; Mateus Sakundarno Adi; M. Arie Wuryanto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Multi Drug Therapy (MDT) for leprosy patient is an efforts to prevent transmission and disability of leprosy. Data of Health Department Office in Blora District in 2015 showed that multibacillary cases have a high proportion than paucibacillary and there found grade 2 disability on new case, this condition may indicates delay treatment of leprosy. This research aimed to describe factors that related to health seeking behaviour of leprosy. This study type was descriptive observational with cross sectional design. Subject of this study were 59 people that recorded as new leprosy patient in 2016 in Blora District. These results indicated the proportion of health seeking behaviour of leprosy with bad category was higher in leper with non productive age (75,0%), male (42,9%), low educational level (50,0%), poor knowledge (52,2%), low income (45,8%), bad attitude (48,3%), poor perception of susceptibility and seriousness of the disease (56,0%), good family support (46,2%) and difficult transportation access (53,6%). This research concluded that proportion of health seeking behaviour of leprosy with bad category found higher in leper with non productive age, male, having low education, having poor knowledge, having low income, having bad attitude, having poor perception of susceptibility and seriousness of the disease, having good family support and having difficult transportation access. PHCs are expected to give more counseling in community about signs, mode of transmission and impact if leprosy untreated, it can be useful to improve health seeking behaviour of leprosy in a good way.